The pragmatic orientation of the advertising text (on a material of the French language) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The article considers advertising as a form of socially oriented communications, characterized by distinct pragmatic purpose. Advertising communication takes connotative function, i. e the creation of the advertising message sender factor takes into account the recipient. Pragmatic bundled with certain functions which ad text performs to obtain the desired effect impact on consumers. By effective remedies consumer phenomena related case law (case text, case statements, case name, case situation), designed for a community of knowledge communicants. The example of the French in the advertising article shows that the implementation of pragmatic functions performed by these texts, promotes the incorporation of social and cultural reference points that exist in a particular society.Pragmatic means possible to name the authors focused selection of linguistic resources, their method of filing and organization skilful combination of linguistic and non-linguistic resources. Compiled advertising text reckoned with the needs of the target audience according to common values, mentality, ideals. Often, advertising texts containing the names of companies, products, serve primarily culturally and socially oriented. To attract the attention of consumers often operate in ad text names of the producers themselves. In some publicity, texts predetermined range of products, thus giving preference to the firm and its products. Advertising conducive to attracting and the culture of other countries, instilling respect for other people, its cultural and national values.
Keywords: advertising text; setting pragmatic; case situation; the target audience; advertising communication; the gender aspect